Voice over LTE via Generic access (Volga) as a possible solution of mobile networks transformation - Stepaniuk, Oleg (Видавництво Львівської політехніки, 2010)
This paper is focused on Voice over LTE via Generic Access Network, which concept is to connect the already existing Mobile Switching Centers to the LTE network via a gateway supporting 2G or 3G voice environment.
Keywords: Voice over LTE via GAN (VoLGA); Generic access Network (GAN); Long Term Evolution (LTE)